Occurrence of Dioctophyma renale in a dog from Valença-RJ: case report - Bastos, Luana (Pubvet, 2020)
Dioctophyma renale is a parasite that affects the kidney of dogs and other species. The infection is acquired by ingestion of larvae that may be present in fish, frogs or aquatic annelids. This parasite is usually found in the right kidney and can also be seen in the left kidney, abdominal cavity, subcutaneous tissue, bladder and rarely in the testicles. The infection is usually asymptomatic and clinical signs such as inappetence, dysuria and renal colic may occur. Diagnosis is made by the presence of parasite eggs in the urine, imaging tests, and in most cases performed by necropsy, or findings during surgical procedures. The recommended treatment is surgical removal of the nematode, in early diagnosed cases, and in late cases, nephrectomy of the affected kidney. This study aimed to report a case of dioctophimosis in a dog in the city of Valença, RJ, where nephrectomy of the affected kidney was performed after parasitosis was diagnosed by ultrasound examination.
Keywords: nephrectomy; parasite; kidney